1991
DOI: 10.1093/nar/19.20.5525
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-DNA glycosylase affects mismatch repair efficiency in transformation and bisulfite-induced mutagenesis inStreptococus pneumoniae

Abstract: The generalized mismatch repair system of Streptococcus pneumoniae (the Hex system) can eliminate base pair mismatches arising in heteroduplex DNA during transformation or by DNA polymerase errors during replication. Mismatch repair is most likely initiated at nicks or gaps. The present work was started to examine the hypothesis that strand discontinuities arising after removal of uracil by uracil DNA-glycosylase (Ung) can be utilised as strand discrimination signals. We show that mismatch repair efficiency is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We believe that the latter interpretation is more likely. Indeed, when transforming pneumococcal DNA contains not only a single mismatch but also other types of (repairable) DNA modifications, the efficiency of the transformation of the low-efficiency marker increases, as would be expected if heteroduplex DNA were formed but other DNA repair activities altered the pattern of mismatch repair (34).…”
Section: Discussionmentioning
confidence: 95%
“…We believe that the latter interpretation is more likely. Indeed, when transforming pneumococcal DNA contains not only a single mismatch but also other types of (repairable) DNA modifications, the efficiency of the transformation of the low-efficiency marker increases, as would be expected if heteroduplex DNA were formed but other DNA repair activities altered the pattern of mismatch repair (34).…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, the mechanism that generate access points for MutS/MutL in the leading strand is currently unknown. Interestingly, in Streptococcus pneumoniae the presence of uracil in the DNA strand that contains the incorrect base increases repair efficiency of mispairs ( Mèjean et al, 1991 ). Furthermore, in B cells of mice and humans, the activation-induced cytidine deaminase (AID) converts cytosine to uracil, generating multiple dU:dG mispairs.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed a time-dependent increase of tandem double mutations until TDM constituted 91% of the total mutants and we have related them directly to the presence of uracil intermediates. Ung has previously been shown to be involved in repair of bisulfite-treated transforming DNA (Mejean et al, 1991;Chen & Shaw, 1993a). The ability to implicate uracil as an intermediate in bisulfite mutagenesis is an important feature of our studies.…”
Section: Discussionmentioning
confidence: 88%